Desain Sistem Kendali pada Ulisar (UUV) Unmanned Underwater Vehicle - Rachim, Vega Pradana; Triwiyatno, Aris; Setiyono, Budi (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Unmanned Underwater Vehicle (UUV) is one of the systems that have a complex characteristic. UUV usually used to obtain data, mapping and underwater survey. One of a complexity that UUV have is based onuncertainty and non-linearity of hydrodynamics parameter. Besides that, UUV which studied in this paper have 6 degree of freedom, so it has also a lot parameter. And to handle that, a bigger system need to divide into some sub-system, the divided is based on control needed. To handle a movement of UUV, it’s important to build a control system that effective and efficient and a writer choose PID and Sliding-PID (SMC-PID) as a controller Modeling system used to linearize a non-linier system from UUV, linearizing around the equilibrium point. Then make a model into a state space, these state space uses for a controlling. For a control system building and respond system from an UUV movement, MATLAB program is needed Keywords: UUV, PID control, Sliding-PID, MATLAB Simulink, Linier System